Comportamiento productivo de cuyes (Cavia porcellus Linnaeus) sexados, alimentados con balanceados comerciales en el cantón Mocache-ecuador - Alcívar Zambrano, Nathaly Silvana (2019)
The research was carried out on the Experimental campus "La María" of the State Technical University of Quevedo (UTEQ), located at km. 7½ of the Quevedo-El Empalme road, Mocache Canton, Los Ríos Province, whose geographical location is 1 ° 3'18 ” south latitude and 79 ° 25 '24' 'west longitude, at a height of 77.60 masl , with a duration of six weeks. The objectives being: To determine the productive behavior of sexed guinea pigs (Cavia porcellus Linnaeus), fed with balanced commercial pellets and determine the profitability of the treatments. A factorial arrangement 2 (sex) x 4 (commercial balances) was applied, within a completely randomized Block Design (DBCA), the initial weight of the experimental units (EU) was blocked, with five repetitions. To determine the statistical differences, the Tukey test (P≤0.05) was used. They were used of 40 guinea pigs (20 males and 20 females) of 35 days of age, with an average weight of 326.6 g. Feed consumption (g), weight gain (g), feed conversion rate, carcass weight (g), carcass yield (%) and profitability were evaluated. Sex (male-female) did not affect the productive response of guinea pigs (P˃0.05). The supply of commercially balanced pellets increases (P˂0.05) weight gain (8.58; 11.89; 12.16 and 11.61g animal-1 day-1), decreases food consumption (122.44; 45.67; 48.75 and 47.49g animal-1 day-1 of DM), improves the food conversion rate (15.93; 4.08; 4.21 and 4.31), carcass weight (440.80; 574.50; 595.40 and 593.10g), carcass yield (65.28; 70.23; 70.72 and 71.23 %) and profitability (3.93; 20.46; 28.65 and 29.11%, in female guinea pigs). There were no differences between pelleted commercial balances (P˃0.05), allowing a commercial weight of 830.0g to be reached at 70 days of age, in the area of influence of the State Technical University of Quevedo (UTEQ). Keywords: nutrition, food, fodder, diets, guinea pigs